2019
DOI: 10.1590/1807-3107bor-2019.vol33.0057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peracetic acid used as single irrigant on the smear layer, adhesion, and penetrability of AH Plus

Abstract: The aim of this study was to evaluate the effect of peracetic acid (PAA) as a single irrigant on the smear layer, on the intraradicular dentinal bond strength, and on the penetrability of an epoxy-based resin sealer into the dentinal tubules. A total of 120 roots were distributed into 4 groups according to the irrigant used in root canal preparation: 1% PAA (PAA); 2.5% NaOCl followed by final irrigation with 17% EDTA and 2.5% NaOCl (NaOCl-EDTA-NaOCl); 2.5% NaOCl (NaOCl); and saline solution (SS). The smear lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…29 About endodontic irrigating solutions, the cytotoxic effect of chemical auxiliary solutions has been increasingly studied. 29,31,32 This study showed that in the various dilutions, the cell viability of 2% PAA remained higher than the solutions of NaOCl 5.25% and CHX 2%, with a statistically significant difference between the groups (p < 0.001). Such results are like those found by other authors demonstrated that 1% PAA showed less cytotoxic effect than 2.5% NaOCl and 17% EDTA.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…29 About endodontic irrigating solutions, the cytotoxic effect of chemical auxiliary solutions has been increasingly studied. 29,31,32 This study showed that in the various dilutions, the cell viability of 2% PAA remained higher than the solutions of NaOCl 5.25% and CHX 2%, with a statistically significant difference between the groups (p < 0.001). Such results are like those found by other authors demonstrated that 1% PAA showed less cytotoxic effect than 2.5% NaOCl and 17% EDTA.…”
Section: Discussionmentioning
confidence: 72%
“…In the present study, there is a great disparity in the results found between the experimental groups 5.25% NaOCl and 2% CHX in comparison to 2% PAA. Although PAA presents positive results for endodontic therapy, such as smear layer removal capacity, 32 and good cell viability, it also demonstrates a significantly lower bacterial decrease than NaOCl and CHX against Enterococcus faecalis biofilm. 38 Thus, its performance as a final irrigator would not improve the disinfection in the irrigation technique.…”
Section: Discussionmentioning
confidence: 99%
“…The root canals were irrigated by 2 mL of 2.5% sodium hypochlorite (NaOCl) (Disineer, Shandong, China) with a 30-gauge side-vented needle (United Dental, Shanghai, China) between each instrument. The final irrigation was 2 mL 17% ethylenediaminetetraacetic acid (EDTA) (Longly, Wuhan, China) for 1 min, followed by 2 mL of 2.5% NaOCl for 1 min and a rinse with 2 mL of saline solution for 1 min[ 24 , 29 ]. Then, the root canals were dried with sterile paper points (Dayading, Beijing, China).…”
Section: Root Canal Preparationmentioning
confidence: 99%
“…Moreover, at 5%, PAA could dissolve pulp tissue equally effectively as 2.5% and 5.25% NaOCl [ 8 ]. Its antibacterial effectiveness accompanied by the capability to eliminate the smear layer has made the PAA a promising irrigant, which would speed up and simplify the preparation of root canal [ 23 ]. In an investigation into the combined use of 0.05% PAA with rotary instruments, Gomes et al [ 24 ] introduced it as an alternative to 2.5% NaOCl for removing the smear layer.…”
Section: Introductionmentioning
confidence: 99%